Women Eat More Rice and Banana: The Influence of Gender and Migration on Staple Food Choice in East Africa. Issue 5 (2nd September 2020) - Bechoff, Aurélie; Forsythe, Lora; Njau, Maria; Martin, Adrienne; Audifas, Gaspar; Abass, Adebayo; Tomlins, Keith
ABSTRACT: An original approach was used to examine how staple food choice differs by gender and migration: this consisted of a quantitative survey (six locations with urban consumers from various economic classes (n = 123)), a qualitative in-depth interview with a subset of those consumers (n = 18), and focus group discussions (n = 13). Men and women had similar results in terms of their preferred staple food choice attributes; yet women indicated consuming more rice and banana, and men, more maize and cassava (Chi-squared test; p < .05). Migration status and life stage (formative or adult years) also influenced the type and diversity of staple crops reported.